The Role of Cash Management Policies in Corporation Governace - Tamar Gamsakhurdia; Ioseb Batiashvili (European Scientific Journal, ESJ, 2017)
Financial management in companies assumed a cash flow management as one of the most important instruments to increase the company's value. The present study has as main objective to carry out a literature review regarding cash flow management policy and to withdraw the main aspects of managing in order to create an objective image upon this indicator. The contribution to current state of research is providing a literature review study, focused on a comparative approach. The results proved that there is no generally accepted definition and cash flow management method, which can be widely used by corporation for achieving the best result of financial performance. The study concluded that raising the quality of knowledge and skills in managing cash flows can be considered as a core ingredient for any business survival and developmental growth.